Inflorescence initiation and development, and the manipulation therof [sic], in selected cultivars of the genus Protea - Gerber, Audrey I. (Audrey Inga) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD(Agric))--University of Stellenbosch, 2000.